الأولياء والسلطة في المغرب الأوسط خلال القرنين (7-8ه / 13/14م) - بن سعود, أم الهناء; خلايفة, سعيدة (جامعة الوادي - University of Eloued, 2023)
ومخلص ما ورد في مذكرتنا هذه هو أن الأولياء في المغرب الاوسط خلال القرنين ال7و8ه-13و14م كان لهم مكانة كبيرة لدى السلطة وتظهر بشكل جلي من خلال المناصب والخطط التي كانوا يعرضونها السلاطين على الاولياء إضافة إلى الهدايا والأموال التي كانوا يقدمونها لهم ويرغبون دائما بالإلتقاء بهم والحضور لمجالسهم ،وذلك لإدراك السلاطين مدى الروابط والعلاقة الشديدة التي تجمع الاولياء بالعامة والهيبة التي صارت لهم لدى الناس باختلاف مستوياتهم واعتقاد الكثير فيهم ، واسهاماتهم في الإصلاح و التكافل الاجتماعي والاهتمام بالفئة المحرومة، ورسوخ ونمو التصوف داخل المجتمع ،وقد عمل الاولياء أيضا على حل الأزمات السياسية والمشاكل الاجتماعية . ورغم المجهودات التي كانوا يقومون بها السلاطين من أجل تقريب الاولياء لهم إلا أن الاولياء ابو الانخراط مع السلطة تحسبا لآخرتهم ولقد استغل أولياء الصوفية هذه المكانة الدينية والروحية والاجتماعية، في قضاء حوائج الناس عند السلطة و التأثير عليها لان أكثر الحكام يعتقدون بهم ،ويخشون عواقب مخالفتهم وهذا بالنسبة للأولياء سند اجتماعي وسياسي . عموما تميزت الفترة المدروسة بحالة من السلم و الاستقرار بين الاولياء والسلطة ولم تكن بينهما نزاعات أو تصادمات كما وقع في زمن المرابطين و الموحدين سابقا .Abstract : Sincerely, what was mentioned in this memorandum is that the saints in the Middle Maghreb during the 7th and 8th centuries AH-13th and 14th centuries AD had a great position in the authority and it appears clearly through the positions and plans that the sultans offered to the saints in addition to the gifts and money that they presented to them and they always wanted to meet with them and attend their councils This is due to the sultans realizing the extent of the ties and strong relationship that unites the saints with the public and the prestige that they have with people of different levels and the belief of many in them, and their contributions to reform and social solidarity and concern for the disadvantaged group, and the consolidation and growth of Sufism within society, and the guardians also worked to solve political crises and social problems . Despite the efforts made by the sultans in order to bring the guardians closer to them, the guardians refused to engage with the authority in anticipation of their afterlife. The saints of Sufism took advantage of this religious, spiritual and social status, in meeting the needs of people with authority and influencing them because most rulers believe in them, and fear the consequences of violating them, and this for saints is a social and political support. In general, the studied period was characterized by a state of peace and stability between the saints and the authority, and there were no conflicts or clashes between them, as happened during the time of the Almoravids and the Almohads previously..
مذكرة ماستر تاريخ تخصص تاريخ الغرب الاسلامي في العصر الوسيط
Keywords: Saints - Power - Middle MaghrebSaadi; الأولياء - السلطة - المغرب الأوسط